PENGARUH DINAMISME LINGKUNGAN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA UMKM DI KOTA MOJOKERTO - Hafid Kholidi Hadi (Jurnal Ilmu Manajemen, 2022)
Micro, Small, and Medium Enterprises (MSMEs) face various challenges from rapidly changing changes. One of the challenges in maintaining and building MSME performance is being able to go through environmental dynamism and environmental uncertainty. This study aims to examine and analyze the relationship between environmental dynamism and environmental uncertainty on the performance of SMEs. Environmental dynamism is measured using customer, competitor, government, and environmental dimensions. Environmental uncertainty includes technological developments, consumer preferences, competitor behavior, disloyal customers, unreliable suppliers, and financial shortages, and MSME performance indicators consist of sales growth, product quality, and product development. Data analysis techniques using PLS-SEM analysis. The selected sample in this study consisted of 100 owners or managers of MSMEs in Mojokerto, Indonesia. The results showed that environmental dynamism and environmental uncertainty had a significant positive effect on the performance of MSMEs. The implication of this research is that environmental uncertainty is not an obstacle to improving MSME performance. Good adaptability is the key for MSMEs to be able to survive in difficult condition.